2019
DOI: 10.3390/su11236749
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Entrepreneurship Holistic Construct

Abstract: In recent years, conducted businesses have been increasingly expected to obtain more sustainable forms, with many added determinants. Indeed, sustainability-related entrepreneurship still faces complex choices among conventional entrepreneurial factors, while being urged to consider three main pillars of sustainability. Thus, this work is focused on the development of sustainability-related entrepreneurship by reflecting the sustainable needs of entrepreneurship. Due to the fact that it is not clear for the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 89 publications
(371 reference statements)
0
17
0
1
Order By: Relevance
“…On the other hand, it affects the impact of this phenomenon, especially in the environmental, social, and economic spheres. Some authors have shown an interest in studying the emerging field of sustainable entrepreneurship [79][80][81][82][83][84][85][86][87][88]. Entrepreneurs are increasingly aware of sustainability, introducing new sustainable services and products to provide social and environmental value [132,133].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it affects the impact of this phenomenon, especially in the environmental, social, and economic spheres. Some authors have shown an interest in studying the emerging field of sustainable entrepreneurship [79][80][81][82][83][84][85][86][87][88]. Entrepreneurs are increasingly aware of sustainability, introducing new sustainable services and products to provide social and environmental value [132,133].…”
Section: Discussionmentioning
confidence: 99%
“…According to Muñoz and Cohen [83] (p. 300), "The recognition of entrepreneurship as a solution to, rather than a cause of, environmental degradation and social inequality moved the field to identify a new type of entrepreneurial activity, namely sustainable entrepreneurship". Sustainable entrepreneurship applies the entrepreneurial approach to achieve societal and environmental goals [81]. Therefore, sustainable entrepreneurship can be defined as "the examination of how opportunities to bring into existence 'future' goods and services are discovered, created, and exploited, by whom, and with what economic, psychological, social, and environmental consequences" [134] (p. 35).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed ontology covers the domain of SE in a form of selected factors and provides a description of EO as a collection of terms and definitions relevant to business enterprises [7], [8]. The ontology was developed also on base of in-depth analysis of available literature presented in [38]. The applied research methodology exploits a previously elaborated bibliometric analysis which included a systematic literature review which was conducted using the PRISMA methodology.…”
Section: Data Collectionmentioning
confidence: 99%
“…The analysis of co-occurrence of keywords was performed using VOSviewer software. The details are included in [38].…”
Section: Data Collectionmentioning
confidence: 99%
“…It will help develop a culture of sensitivity and re-design of business models to turn to a more effective system. Such a mechanism results in improved performance in terms of environmental, social and economic dimensions and enhances the chances of a firm's survival [49].…”
Section: Sustainable Entrepreneurial Orientation (Seo) and Sustainablmentioning
confidence: 99%